Postpartum Contraception: a Comparative Study of Berlin Women with and without Immigration Background - David, M. (Geburtshilfe Frauenheilkd, 2015)
Research Questions: Are there differences in postpartum contraceptive use between women with and without immigration background? Do women more commonly use contraception following a high-risk pregnancy or caesarean section? What role does current breastfeeding play and, amongst immigrants, what is the effect of acculturation level on the frequency of contraceptive use? Study Population and Methods: Data collection was carried out as part of a larger study in three Berlin delivery units using standardised interviews (questionnaires covering e.g. sociodemographics, immigration history/acculturation and use of antenatal care); telephone interviews comprising 6 questions on postpartum contraception, breastfeeding and postpartum complications were conducted on a sample of the study population six months after delivery. Results: 247 women with, and 358 women without a background of immigration were included in the study (total study population n = 605, response rate 81.1 %). 68 % of 1st generation immigrants, 87 % of 2nd/3rd generation women and 73 % of women without immigration background (non-immigrants) used contraception. In the logistical regression analysis 1st generation immigrants were less likely than non-immigrants to be using contraception six months postpartum, and 1st generation immigrants with low acculturation level were significantly less likely to use contraception than 2nd/3rd generation women with low acculturation level. Conclusion: In the extended postpartum period there was no major difference in contraceptive use between immigrants in general and non-immigrants. It remains unclear whether the differing contraceptive behaviour of 1st generation immigrants is the result of less access to information, sociocultural factors or differing contraceptive requirements and further targeted, qualitative study is required.